Toward safer digital sexual health communication: evaluating the public health reliability of large language model responses on sexually transmitted infections - Shucheng Zhang; Shuo Wang; Xiaoyue Sun; Zhuqing Li; Yang Lin; Jiale Geng; Xiaoqing Si (Frontiers in Public Health, 2026)
Background The global burden of sexually transmitted infections (STIs) continues to rise, yet stigma drives many to seek sensitive health information from artificial intelligence chatbots. The quality, safety, readability, and destigmatization of large language model (LLM) responses on sexual health remain under-evaluated, particularly for non-Western models. Methods This cross-sectional study constructed 30 standardized English queries (5 themes × 6 questions) informed by Google Trends, Centers for Disease Control and Prevention (CDC) guidelines, and patient education platforms, and submitted them to three LLMs—GPT-5.4, DeepSeek-V4-Pro, and Kimi K2.6—via official APIs, in duplicate (180 responses). Two dermatovenereologists (>10 years' experience) rated the responses while blinded to platform identity, across six dimensions (accuracy, completeness, safety, understandability, actionability, and destigmatization) using a five-point scale, supplemented by four readability metrics (FKGL, FRE, GFI, and SMOG). Primary analysis used linear mixed-effects models retaining all individual ratings; the original aggregated non-parametric pipeline was retained as a sensitivity analysis. Reliability used ICC and quadratic-weighted Cohen's κ with 95% CIs; correlations used query-level cluster bootstrap with false-discovery-rate control. Results Inter-platform differences were significant for accuracy (χ 2 (2) = 19.12, Holm-adjusted P < 0.001), understandability (χ 2 (2) = 13.54, P = 0.006), and destigmatization (χ 2 (2) = 9.16, P = 0.041). GPT-5.4 and Kimi K2.6 achieved the highest accuracy (both median 5.00), both significantly above DeepSeek-V4-Pro and not significantly different from each other. DeepSeek-V4-Pro and Kimi K2.6 both used significantly more destigmatizing language than GPT-5.4, with no significant difference between them. GPT-5.4 produced the least readable text on all four metrics (all adjusted P < 0.01). Inter-rater reliability was good to excellent (ICC(2, 1) = 0.79–0.95; quadratic-weighted κ = 0.79–0.95). Conclusions The three LLMs showed distinct profiles: GPT-5.4 and Kimi K2.6 achieved the highest accuracy, whereas GPT-5.4 produced the least readable outputs; DeepSeek-V4-Pro and Kimi K2.6 used more destigmatizing language. To our knowledge, this is the first study to quantify destigmatizing language as an explicit evaluation dimension for LLM-generated STI content, albeit as an exploratory measure pending formal content validation. Findings are specific to these models and queries and can inform quality standards and monitoring for safer AI-powered sexual health communication.